Central banking and financialization a Romanian account of how Eastern Europe became subprime - Gabor, Daniela (Studies in economic transition, 2010)
This book explores the causes and effects of the rise of neoliberalism in Eastern Europe in the aftermath of the collapse of the Soviet Union. It provides a political economy analysis of the role of central banks, and identifies them as a key actor in the production and dissemination of the neoliberal economic policies